(untitled) (PENDAIS, 2024)
TPACK (Technological Pedagogical Content Knowledge) is a framework that provides an overview of the relationship and complexity among 3 (three) basic components of knowledge (technology, pedagogy, and content). Technological pedagogical content knowledge (TPACK): TPACK deals with the knowledge required by teachers to integrate technology into the teaching of specific content. Technological pedagogical knowledge (TPK): knowledge of how various technologies can be used in teaching, and to understand that using technology can change the way teachers teach. Technological pedagogical content knowledge (TPACK): intuitive knowledge of complex interactions among the three basic components of knowledge (CK, PK, TK) by teaching content using appropriate pedagogical methods and technologies. TPACK is a useful framework for thinking about what knowledge teachers should have to integrate technology into teaching and how they develop this knowledge. Using TPACK as a framework to measure teaching knowledge will have an impact on the type of training and professional experience development designed for aspiring teachers and teachers. Keywords: TPACK